Pore surface engineering in porous, chemically stable covalent organic frameworks for water adsorption - Biswal, Bishnu P.; Kandambeth, Sharath; Chandra, Suman; Shinde, Digambar Balaji; Bera, Saibal; Karak, Suvendu; Garai, Bikash; Kharul, Ulhas K.; Banerjee, Rahul (Journal of Materials Chemistry A, 2015)
Herein, we have explored the possibility of a class of covalent organic frameworks (COFs) as water adsorbing materials. We have selected, synthesized 12 chemically stable functionalized Schiff base COFs and thoroughly studied their water uptake behaviour. Further, a deep understanding was developed with these COFs towards the effects of condensation pressure of water and hydrophilic/hydrophobic groups present in the COF pores on water absorption capacity and ultimately, their recyclability. Among all reported COFs, TpPa-1 shows the highest water uptake of 30 wt% (368 cm(3) g(-1); 17 mmol g(-1)) at P/P-0 = 0.3, which is also comparable with the recently reported carbon materials and few well known MOFs. This study also reveals that the overall water uptake of COFs can be tuned systematically based on chemical functionality and pore size in a wider window of relative pressures.

Porosity switching in polymorphic porous organic cages with exceptional chemical stability - Bera, Saibal; Dey, Kaushik; Pal, Tapan K.; Halder, Arjun; Tothadi, Srinu; Karak, Suvendu; Addicoat, Matthew; Banerjee, Rahul (Angewandte Chemie-International Edition, 2019)
Porous solids that can be switched between different forms with distinct physical properties are appealing candidates for separation, catalysis, and host-guest chemistry. In this regard, porous organic cages (POCs) are of profound interest because of their solution-state accessibility. However, the application of POCs is limited by poor chemical stability. Synthesis of an exceptionally stable imine-linked (4+6) porous organic cage (TpOMe-CDA) is reported using 2,4,6-trimethoxy-1,3,5-triformyl benzene (TpOMe) as a precursor aldehyde. Introduction of the -OMe functional group to the aldehyde creates significant steric and hydrophobic characteristics in the environment around the imine bonds that protects the cage molecules from hydrolysis in the presence of acids or bases. The electronic effect of the -OMe group also plays an important role in enhancing the stability of the reported POCs. As a consequence, TpOMe-CDA reveals exceptional chemical stability in neutral, acidic and basic conditions, even in 12m NaOH. Interestingly, TpOMe-CDA exists in three different porous and non-porous polymorphic forms (, , and ) with respect to differences in crystallographic packing and the orientation of the flexible methoxy groups. All of the polymorphs retain their crystallinity even after treatment with acids and bases. All the polymorphs of TpOMe-CDA differ significantly in their properties as well as morphology and could be reversibly switched in the presence of an external stimulus.
Keywords: chemical stability; Morphology; organic cages; polymorphism; porosity switching